Cerebral palsy - Aaseng, Nathan (New York : F. Watts, 1991)
Discusses the causes, effects, prevention, and treatment of the debilitating condition known as cerebral palsy, which may occur in many different forms.
Includes bibliographical references (p. 89-90) and index.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
7-10.
Young Adult
Keywords: Cerebral palsy; Cerebral palsy; Physically handicapped; Cerebral palsy; Physically handicapped